2017
DOI: 10.18203/issn.2454-2156.intjscirep20170886
|View full text |Cite
|
Sign up to set email alerts
|

Communication skills (verbal, listening, feedback) among Ardabil Azad university medical students and related factors

Abstract: INTRODUCTIONRelation is said to the interaction between human which have done to estimate a specific purpose and establish a proper relationship that can be very important in people's lives. In studies of medical sciences, communicating takes place with specific purposes, such as teaching the patients, collecting clinical evaluation and assessment of possible treatment. Having CS between people is very important. Communication skills (CS) means listening and speaking relation between two persons and its feedba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
2
1
1
Order By: Relevance
“…These findings were in contrast with a descriptive cross-sectional study in Iran that assessed communication skills (verbal, listening, feedback) among Ardabil Azad University medical students, along with related factors [11], as this study concluded that the communication skills among the students were at a moderate level. This could be explained by the difference in the target population and years of study, as our students in the first year, but in the other study, the students were selected randomly from all university medical students.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings were in contrast with a descriptive cross-sectional study in Iran that assessed communication skills (verbal, listening, feedback) among Ardabil Azad University medical students, along with related factors [11], as this study concluded that the communication skills among the students were at a moderate level. This could be explained by the difference in the target population and years of study, as our students in the first year, but in the other study, the students were selected randomly from all university medical students.…”
Section: Discussioncontrasting
confidence: 99%
“…1 Also, in many studies, the relation between CS and variables such as age, gender and education level was significant which not in line with our study results was. [9][10][11][12][13][14] In this study, there was a positive correlation between verbal skill and feedback (r=0.4, P=0.001) but the relation between verbal skill and listening and also the relation between listening skill with feedback wasn't significant.…”
Section: Resultsmentioning
confidence: 90%
“…In other studies in Iran, all of correlation between three dimension of CS was positive and significant which was some different to our study results. 1,10,12,14 In this study there was a significant difference in verbal skill score between women and men staff and nurses (18.9±3.6 versus 17.2±4.2, P=0.001) but the difference in total CS score and other two dimension of CS (listening and feedback) score between two sexes wasn't significant which was not in line with other studies, because in Barati et al study in Hamadan and also other studies in Iran, the total score of CS in women staff was significantly more than men staff. 1,11,12,14…”
Section: Resultsmentioning
confidence: 99%
“…tarafından yapılan çalışmada iletişim becerileri, sosyodemografik değişkenlerine göre incelenmiştir (26). Bu araştırmanın sonuçlarına göre anne ve baba eğitim düzeyi ile iletişim becerileri arasında anlamlı bir ilişkiye rastlanmamıştır ancak cinsiyet ve sınıf değişkenleri ile iletişim puanları arasında ise anlamlı bir farklılık saptanmıştır (26) (27). Diş hekimliği stajyer öğrencileri ile yapılan çalışmada da cinsiyet bakımından anlamlı bir fark elde edilmemiştir (28).…”
Section: Gereç Ve Yöntem Araştırmanın Tipiunclassified